2021
DOI: 10.3389/fmed.2021.749569
|View full text |Cite
|
Sign up to set email alerts
|

IL 33 Correlates With COVID-19 Severity, Radiographic and Clinical Finding

Abstract: Objective: The increased level of interleukin (IL)-33 is considered as a predictor of severe coronavirus disease 2019 (COVID-19) infection, but its role at different stages of the disease is still unclear. Our goal was to analyze the correlation of IL-33 and other innate immunity cytokines with disease severity.Methods: In this study, 220 patients with COVID-19 were included and divided into two groups, mild/moderate and severe/critical. The value of the cytokines, clinical, biochemical, radiographic data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
1
27
2
Order By: Relevance
“…Hadjadj et al reported that plasma levels of IFN-α2 decreased with disease severity, but were not significantly different compared to healthy controls (71). Our results are different from a plasma study which reported higher IL33 in severe COVID-19 cohort but our findings are consistent with a nasopharynx study (70, 72). IL-13 was also not significantly different from healthy controls in our samples, in contrast to a previous report (56).…”
Section: Discussioncontrasting
confidence: 97%
“…Hadjadj et al reported that plasma levels of IFN-α2 decreased with disease severity, but were not significantly different compared to healthy controls (71). Our results are different from a plasma study which reported higher IL33 in severe COVID-19 cohort but our findings are consistent with a nasopharynx study (70, 72). IL-13 was also not significantly different from healthy controls in our samples, in contrast to a previous report (56).…”
Section: Discussioncontrasting
confidence: 97%
“…Hadjadj et al reported that plasma levels of IFN-α2 decreased with disease severity but were not significantly different compared to healthy controls (71). Our results are different from a plasma study that reported higher IL-33 in a cohort with severe COVID-19, but our findings are consistent with a nasopharynx study (70,72). IL-13 was also not significantly different from healthy controls in our samples, in contrast to a previous report (56).…”
Section: Discussioncontrasting
confidence: 94%
“…In one of the first studies, Burke H et al revealed increased levels of the IL-33 as a significant predictive marker of adverse outcome in COVID-19 patients [ 205 ]. Following observations similarly demonstrated its elevated levels that were correlated with clinical and radiographic parameters of the disease and established its positive correlation with TNF-α, IL-1β, IL-6, IL-12, and IL-23 levels and its negative correlation with O2 saturation of the COVID-19 patients [ 206 , 207 ] (Table 1 ). Additionally, elevated levels of the IL-33 together with IL-18 were coupled with higher concentrations of the renal toxicity markers such as glutathione S-transferase (GST) and osteopontin in COVID-19 patients, which confers its putative interference in multi-systemic damages of the SARS-CoV-2 infection [ 208 ].…”
Section: Il-33 and Covid-19mentioning
confidence: 80%